Metode New Information Economics untuk Menganalisis Manajemen Departemen Teknologi Informasi PT. Teijin Indonesia Fiber Corporation (TIFICO), Tbk. Tangerang - Hudiarto, Hudiarto; Raditya, Hernanda; Supriyatna, Cecep; Amrin, Muhammad Ichsan (Bina Nusantara University, 2011)
PT. TIFICO, Tbk., Tangerang is a company engaged in the textile industry that produces fiber and yarn. It has several application systems, infrastructure, services, ongoing management and application projects to be developed to improve its business processes. The company?s management wants to discern the interest and suitability level of each applications upon the company needs and want to know whether the issued investments matches up the impact and benefits to the company. The author proposes to analyze the running application system and IS/IT project plans using only 4 tools of the New Information Economics method: strategic demand/supply planning, innovation, prioritization and alignment. The results obtained is information about investment strategy of the ERP system Oracle E-Business Suite implementation and project plans to discern which IS/IT is more important to be developed and which one should be ignored, so that the company can allocate the investments to the IS/ IT projects that best support the company's operation.